The Operational Procedures Good Fish Quarantine Standards For Export Marine Ornamental Fish At PT Banyu Biru Sentosa, Tanggerang - Wahyuni Zam; Mauli Kasmi; Alfina Damayanti; Sitti Fakhriyyah (Citakonsultindo, 2023)
The carnivorous fish is one of the many commercial commodities of the sea and is of great interest to the public because of its many varieties and diverse features.The objective of the problem of the latter is to optimize the use of the soup in see-based fish maintenance to be made available at the Indonesian stock exchange.Based on the formula and goals to be achieved in this final assignment the type of data used that is secondary and primary data data with data collection techniques done are interviews, library studies, and observations.According to the last job this can be established to demonstrate optimally the maintenance standards of the oinfish procedure to improve the quality of the sea fish, administer ckib as appropriate, maintain the quality of the water by paying attention to salinity, temperature and ph of the water, maintain the quality of feed, regularly conduct water spines, regularly conduct disinfectant for maintenance of the fish.